Emergence of Omentin as a Pleiotropic Adipocytokine - Jaikanth, C.; Gurumurthy, P.; Cherian, K. M.; Indhumathi, T. (Experimental and Clinical Endocrinology & Diabetes, 2013)
“Less is more” – this is becoming the global quote on event of alarming rise in the prevalence of obesity among all age groups. The perspective of adipose tissue as merely a fat depot has changed in recent times. Focus is now being laid on the metabolic and inflammatory functions of the adipose tissue which is modulated through adipocytokines. Adipocytokines have been found to control insulin sensitivity, inflammatory activity, neuroendocrine activity, cardiovascular function, food and water intake, breeding, and bone metabolism. Few of these adipokines play a role in the positive metabolism promoting good health, while few of them pose adverse effects. Omentin is a recently identified novel adipocytokine and it falls under the category of being a good adipokine. Plasma omentin-1 levels are significantly decreased in patients with obesity, insulin resistance, and diabetes that contribute to the major components of the metabolic syndrome and other disease conditions like atherosclerosis, autoimmune disorders etc and that the review focuses on the comprehensive effects of omentin on all the major systems of the body.
Keywords: omentin; adipocytokine; metabolism; cardiovascular diseases